Limitations and recommendations regarding the Mini-Mental State Examination (MMSE) in illiterate and low educated older adults - Mandyla, Maria-Aikaterini; Kosmidis, Mary H. (Psychology: the Journal of the Hellenic Psychological Society, 2023)
Increasing life expectancy has been associated with higher rates of dementia. As illiterate/uneducated individuals are typically over-represented among older cohorts, it is imperative that we identify and/or develop appropriate, non-biased scales and psychometric tests for early detection of, and screening for, cognitive impairment in this group. Given that many traditional neuropsychological tests may underestimate cognitive abilities in illiterate/uneducated and low educated individuals, their use in these groups needs to be reappraised or their format adapted. One of the most commonly used screening tests worldwide is the Mini-Mental State Examination (MMSE). Level of education has been shown to be a significant predictor of performance on the MMSE, hence, there is dispute among researchers related to its applicability in populations with low or no schooling. A wide range of recommendations have been made by scholars for overcoming the education effect on the MMSE, as well as other sources of bias, but some methodological limitations remain, and new ones have emerged concerning its administration to illiterate/uneducated and low educated older individuals. In the present study, we present a theoretical discussion of the challenges inherent in the administration and interpretation of MMSE performance in illiterate/uneducated and low educated individuals, consider previous recommendations and address their limitations, and highlight the optimal methods for clinical assessment of these groups when the MMSE is used.